Analysis of Relationship Between Some Disazo Dyes Derived from 2,4-Dihydroxyquinoline and Its Anticancer and DNA Binding Properties by Density Functional Theory - Nesrin Şener; Muhammet Çavuş (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2021)
It was studied some physical and chemical properties of 2,4-dihydroxy quinoline derivative diazo dyes by theoretical methods. Six different solvents were used to determine the solvatochromic behavior and absorption of the compounds, and the experimental results were compared with the theoretical data obtained from quantum chemical calculations. DFT calculations were carried out to obtain the geometric, electronic and some chemical reactivity parameters of the compounds. The atom in molecule, natural bond orbital, density of state, non-covalent interaction, Fukui function, electron localization function, and electron delocalization range analyzes of the compounds were performed to determine the relationship between the electronic properties and the DNA binding capacity and the cytotoxicity against HeLa and PC3 cancer cell lines. It was observed that the compounds substituted with –Cl and –NO2 had higher DNA binding and higher anticancer effect. Besides the positions of the substituents, the electron density in the bonds, the delocalization index values and the distribution of the nucleophilic and electrophilic attack sites are among the important factors determining the reactivity of the compounds. In addition, the HOMO energies of the compounds with better DNA binding properties were calculated higher than the other compounds.